Digital Atlas «Snow and Ice on the Earth» - T. Y. Khromova; A. A. Medvedev; A. Ya. Muraviev; N. M. Zverkova (Лëд и снег)
Results of the work done on creating the digital glaciological atlas are discussed. The prerequisites for and the techniques of the Atlas preparation together with its structure, content, and the ways of the use are presented.